Fast recovery from Peripheral Facial Palsy in a patient with Ramsay-Hunt Syndrome using Photobiomodulation Therapy - Ballardin,Bárbara Soldatelli (2023)
Abstract Ramsay-Hunt syndrome is an infectious disease associated with the varicella-zoster virus, and peripheral facial palsy is often one of its clinical manifestations. This case report describes a patient diagnosed with Ramsay-Hunt syndrome who developed peripheral facial palsy and was treated by photobiomodulation therapy. A 26-year-old woman developed a lack of facial mobility on the right side, asymmetry, otalgia, dysgeusia, and dry eyes, leading to the diagnosis of Ramsay-Hunt syndrome. Her peripheral facial palsy was classified as moderately severe according to the House-Brackmann scale. Acyclovir, prednisone, and physiotherapy sessions were prescribed to manage peripheral facial palsy. In the absence of a clinical response to the proposed therapies, photobiomodulation therapy was employed using the parameters: 780 nm, 100 mW, 3 J/point, and 30.48 J/cm2. After five sessions of photobiomodulation therapy, complete recovery of facial movement was observed. Photobiomodulation therapy treated peripheral facial palsy effectively, allowing a fast recovery and avoiding irreversible sequelae in a patient with Ramsay-Hunt syndrome.